Movement of cerebrospinal fluid tracer into brain parenchyma and outflow to nasal mucosa is reduced at 24 h but not 2 weeks post-stroke in mice - K. E. Warren; K. G. Coupland; R. J. Hood; L. Kang; F. R. Walker; N. J. Spratt (Fluids and Barriers of the CNS, 2023)
Abstract Background Recent data indicates that cerebrospinal fluid (CSF) dynamics are disturbed after stroke. Our lab has previously shown that intracranial pressure rises dramatically 24 h after experimental stroke and that this reduces blood flow to ischaemic tissue. CSF outflow resistance is increased at this time point. We hypothesised that reduced transit of CSF through brain parenchyma and reduced outflow of CSF via the cribriform plate at 24 h after stroke may contribute to the previously identified post-stroke intracranial pressure elevation. Methods Using a photothrombotic permanent occlusion model of stroke in C57BL/6 adult male mice, we examined the movement of an intracisternally infused 0.5% Texas Red dextran throughout the brain and measured tracer efflux into the nasal mucosa via the cribriform plate at 24 h or two weeks after stroke. Brain tissue and nasal mucosa were collected ex vivo and imaged using fluorescent microscopy to determine the change in CSF tracer intensity in these tissues. Results At 24 h after stroke, we found that CSF tracer load was significantly reduced in brain tissue from stroke animals in both the ipsilateral and contralateral hemispheres when compared to sham. CSF tracer load was also reduced in the lateral region of the ipsilateral hemisphere when compared to the contralateral hemisphere in stroke brains. In addition, we identified an 81% reduction in CSF tracer load in the nasal mucosa in stroke animals compared to sham. These alterations to the movement of CSF-borne tracer were not present at two weeks after stroke. Conclusions Our data indicates that influx of CSF into the brain tissue and efflux via the cribriform plate are reduced 24 h after stroke. This may contribute to reported increases in intracranial pressure at 24 h after stroke and thus worsen stroke outcomes.